Chinese Buddhism in Africa: The Entanglement of Religion, Politics and Diaspora - Shi, Xuefei (Contemporary buddhism, 2023)
This article delves into the advent of Chinese Buddhism in Africa and its entanglement with politics and the contemporary Chinese transnationalism. It explores the previously uncharted territory of the endeavours of Chinese Buddhist organisations and the transnational elements of Chinese religions in Africa. Drawing on ethnographic data from South Africa, Tanzania, Botswana and Malawi, this article examines the mobility of transnational Chinese Buddhism, probes retrospectively into its origins and drives, and investigates its connections with the evolving China-Africa/Taiwan-Africa engagements. We argue that contemporary Chinese Buddhism in Africa is a product of connections and competitions between states, African politics, and the multi-layered Chinese diaspora. The political, social and cultural influences of transnational Chinese Buddhists in Africa warrant further exploration and analysis.